Vascular imbalance in polycystic ovary syndrome: Insights into endothelial dysfunction - Tuğba Raika Kıran; Mehmet Erdem; Engin Yıldırım; Feyza İnceoğlu (PLoS ONE, 2025)
Polycystic ovary syndrome (PCOS) is a multifactorial endocrine disorder associated with vascular dysfunction and increased cardiovascular risk. This study aims to investigate the dysregulation of vascular tone in PCOS, focusing on the imbalance between vasodilators (nitric oxide [NO] and apelin) and vasoconstrictors (noradrenaline and reduced prostacyclin). By examining these factors, the study seeks to elucidate their contribution to endothelial dysfunction and cardiovascular complications in PCOS patients. Forty-four patients diagnosed with PCOS according to the 2003 Rotterdam Criteria, along with 44 healthy controls, were included in the study. Ultrasound evaluations were performed on all volunteers. Serum NO, apelin, noradrenaline, and prostacyclin levels were measured using commercial enzyme-linked immunosorbent assay (ELISA) kits. Additionally, routine biochemical, hormonal, and glycated hemoglobin analyses were conducted on all samples. There was no statistically significant difference between the PCOS and control groups in terms of marital status, age, and body mass index (BMI) (p > 0.05). Compared to the control group (83.85 ± 22.65 µmol/L, 190.88 ± 16.44 ng/L, and 24.63 ± 4.59 ng/L, respectively), NO, apelin, and noradrenaline concentrations were significantly higher in patients with PCOS (104.35 ± 44.96 µmol/L, 379.57 ± 40.11 ng/L, and 27.48 ± 5.36 ng/L, respectively) (p < 0.01). In contrast, prostacyclin concentrations were significantly lower in patients with PCOS (5.85 ± 1.28 ng/L) compared to the control group (6.78 ± 1.99 ng/L) (p = 0.011). Additionally, a statistically significant difference was found between the PCOS and control groups in FSH, LH, testosterone, SHBG, glucose, and HDL levels (p < 0.05). The disrupted balance between vasodilation and vasoconstriction in PCOS, driven by altered levels of NO, apelin, noradrenaline, and prostacyclin, contributes to endothelial dysfunction and increased cardiovascular risk. These molecular disturbances underline the need for targeted therapeutic strategies aimed at restoring vascular homeostasis in PCOS patients.